Autoriti hadith dalam kitab Tasawuf tulisan Jawi: satu kajian terhadap kitab hidayah Al-Salikin' - Ahmad, Khadher; Suliaman, Ishak (Brill Academic Publishers, 2007)
The study aims to analyze the quality of Hadith in the books of neo-sufism, especially the Malay version. Syeikh 'Abdul Samad al-Falimbani's Hidayah al-Salikin which is deeply influenced by the tasawwuf of al-Ghazali is analyzed thoroughly in terms of its history including of the author himself, approach, content as well as its language. From the analysis,the quality of the Hadiths in the book are established.